Effects of Increased Vitamin Premix Inclusion Rate on Growth Performance of Finishing Pigs - Hilario M. Cordoba; Robert D. Goodband; Joel M. DeRouchey; Mike D. Tokach; Jason C. Woodworth; Jordan T. Gebhardt (Kansas Agricultural Experiment Station Research Reports, 2022)
A total of 1,080 mixed sex pigs (337 × 1050, PIC; initially 63.1 ± 0.87 lb) were used in a 123-d growth trial to determine the effects of vitamin premix inclusion rate on growing-finishing pig growth performance and carcass characteristics. Pens of pigs were assigned to 1 of 2 treatments in a completely randomized design. There were 20 replicate pens/treatment and 27 pigs/pen. The experimental diets were corn-soybean meal-based and were fed in 4 phases from 63 to 110, 110 to 160, 160 to 220, and 220 to 293 lb. Pigs were fed 1 of 2 levels of a vitamin premix (control and double) that contained: 750,000 IU vitamin A acetate; 300,000 IU vitamin D; 8,000 mg vitamin E (dl-α-tocopheryl acetate); 600 mg vitamin K (menadione); 6 mg vitamin B₁₂; 9,000 mg niacin; 5,000 mg pantothenic acid; and 1,500 mg riboflavin per lb. The inclusion rate per phase was 3, 2.5, 2, and 1.5 lb/ton, respectively, for the control, or the same premix added at double rate in each phase for the high vitamin fortification. Overall (d 0 to 123), there was no evidence for difference (P>0.10) in ADG, ADFI, and F/G. Also, no statistical difference was observed (P>0.10) for final BW, HCW, or any carcass characteristic. In conclusion, doubling the inclusion rate of a common vitamin premix did not influence growth and carcass traits in growing-finishing pigs.
Keywords: growth performance; finishing pigs; vitamins